2013
DOI: 10.11646/zootaxa.3609.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of philometrid nematodes (Nematoda: Philometridae) in Epinephelus coioides (Hamilton, 1822) from the South Bali Sea, Indonesia

Abstract: Based on light and scanning electron microscopy, two new species of philometrid nematodes, Spirophilometra endangae sp. nov. and Philometra epinepheli sp. nov. (Nematoda: Dracunculoidea: Philometridae) are described from Epinephelus coioides (Hamilton, 1822) (Perciformes: Serranidae) from the South Bali Sea, Indonesia. Spirophilometra endangae sp. nov. was isolated from the fins of E. coioides. The new species can be distinguished from the most closely related S. eichleri Parukhin, 1971 by a larger total body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Taxonomical and ecological studies on fish parasites from Indonesia have been intensified in recent years (e.g. Palm et al , 2007, 2008, 2011; Yuniar et al , 2007; Palm, 2008, 2011; Bray & Palm, 2009; Kuchta et al , 2009; Rückert et al , 2009a, b, 2010; Kleinertz, 2010, Kleinertz et al , 2012, Dewi & Palm, 2013; Kuhn et al , 2013), taking into account the high parasite biodiversity at this tropical location. The purpose of the present study is an assessment of the fish parasite fauna of E. coioides , a widely distributed and rapidly developing mariculture species in Indonesia, from additional sampling sites.…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomical and ecological studies on fish parasites from Indonesia have been intensified in recent years (e.g. Palm et al , 2007, 2008, 2011; Yuniar et al , 2007; Palm, 2008, 2011; Bray & Palm, 2009; Kuchta et al , 2009; Rückert et al , 2009a, b, 2010; Kleinertz, 2010, Kleinertz et al , 2012, Dewi & Palm, 2013; Kuhn et al , 2013), taking into account the high parasite biodiversity at this tropical location. The purpose of the present study is an assessment of the fish parasite fauna of E. coioides , a widely distributed and rapidly developing mariculture species in Indonesia, from additional sampling sites.…”
Section: Introductionmentioning
confidence: 99%
“…coioides in the South Bali Sea, Indonesia [2]. Subsequently, the same two species were recorded in E .…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies carried out in adjacent waters off southern Indonesia and northern Australia by Moravec et al [27], Dewi & Palm [2] and Moravec & Diggles [16] revealed the presence of several previously unknown philometrids in marine fishes, which may also occur in the New Caledonia region. Additional samples of philometrid nematodes, including three new species of Philometra , were collected from carangid and serranid perciform fishes.…”
Section: Introductionmentioning
confidence: 99%
“…For the ectoparasites, identification followed Whittington, Deveney, and Wyborn (), Dang, Levsen, Schander, and Bristow () (Monogenea), Bruce () (Isopoda), Ho and Lin () Ho, Liu, and Lin () (Copepoda). For the endoparasites, identification followed Bray and Cribb (), Bray and Palm (), Bray and Justine (), Yamaguti (, ) (Digenea), Palm () (Cestoda), Moravec, Justine, and Rigby (), Anderson, Chabaud, and Willmott (), Dewi and Palm (), Gibbons () (Nematoda), Lom and Dyková (, ) and Vo et al. () (Protozoa).…”
Section: Methodsmentioning
confidence: 99%